Doctor Zhivago - Bolt, Robert; Ponti, Carlo; Lean, David; Sharif, Omar; Pasternak, Boris Leonidovich (Burbank, CA : Warner Home Video, 2001)
A poet and surgeon, husband and lover finds his life disrupted by war. It alters the lives of many, including Tonya, the gentle woman he marries and Lara, the woman he cannot forget.
Special features: Introduction by Omar Sharif; commentary by Omar Sharif, Rod Steiger, and Sandra Lean; music-only track; interactive menus; theatrical trailer; scene access; 10 vintage documentaries.
Based on the novel by Boris Pasternak.
Disc A: dual-layer format.
Keywords: Feature films; Films for the hearing impaired